2015
DOI: 10.1101/gad.252734.114
|View full text |Cite
|
Sign up to set email alerts
|

PRDM16 binds MED1 and controls chromatin architecture to determine a brown fat transcriptional program

Abstract: PR (PRD1-BF1-RIZ1 homologous) domain-containing 16 (PRDM16) drives a brown fat differentiation program, but the mechanisms by which PRDM16 activates brown fat-selective genes have been unclear. Through chromatin immunoprecipitation (ChIP) followed by deep sequencing (ChIP-seq) analyses in brown adipose tissue (BAT), we reveal that PRDM16 binding is highly enriched at a broad set of brown fat-selective genes. Importantly, we found that PRDM16 physically binds to MED1, a component of the Mediator complex, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 37 publications
10
115
0
2
Order By: Relevance
“…We found that EBF2 binds to ∼28,000 sites in the genome (Supplemental Excel File 1), many of which are in regions near brown fat-specific genes that show characteristic enhancer marks in BAT but not white adipose tissue (WAT) ( Fig. 1A; Harms et al 2015). A de novo motif search within EBF2-binding sites identified EBF as the top enriched motif, which validates the specificity of our ChIP-seq results (Supplemental Fig.…”
Section: Ebf2 Regulates Chromatin Accessibility At Brown Fat-specificsupporting
confidence: 78%
See 1 more Smart Citation
“…We found that EBF2 binds to ∼28,000 sites in the genome (Supplemental Excel File 1), many of which are in regions near brown fat-specific genes that show characteristic enhancer marks in BAT but not white adipose tissue (WAT) ( Fig. 1A; Harms et al 2015). A de novo motif search within EBF2-binding sites identified EBF as the top enriched motif, which validates the specificity of our ChIP-seq results (Supplemental Fig.…”
Section: Ebf2 Regulates Chromatin Accessibility At Brown Fat-specificsupporting
confidence: 78%
“…S1F). We performed genome-wide analysis anchoring on previously defined adipose depot-selective genes and regulatory regions (Supplemental Excel File 2; Harms et al 2015). On a genome-wide scale, loss of Ebf2 reduced RNA Pol II gene body occupancy and H3K27ac levels at brown fat-selective regulatory regions and increased Pol II and H3K27ac levels at white fat genes and regulatory regions (Fig.…”
Section: Ebf2 Regulates Chromatin Accessibility At Brown Fat-specificmentioning
confidence: 99%
“…These observations suggest that there is a mechanism that is preventing LSD1 from demethylating and inducing repression of those BAT-selective genes even if LSD1 is brought into close proximity together with PRDM16. Two reports showed that PRDM16 activates transcription of BAT-selective genes by recruiting MED1, a component of the mediator complex, to enhancer regions nearby (Harms et al 2015;Iida et al 2015). It is possible that the corecruitment of MED1 or additional members of the mediator complex by PRDM16 alters the enzymatic activity or substrate accessibility of LSD1 to render it nonoperative at loci near BAT-selective genes.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR␥ ChIP-seq in 3T3-L1 is from GEO accession number GSE27450 (40), PPAR␥ ChIP-seq in EWAT is from GEO accession number GSE64458 (41), and PPAR␣ ChIP-seq in liver is from accession number GSE61817 (42). Histone 3 lysine 27 acetylation ChIP-seq in EWAT is from GEO accession number GSE63964 (43).…”
Section: Methodsmentioning
confidence: 99%